(untitled) (Research, Society and Development, 2025)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has highlighted the urgent need for effective therapeutic strategies. While antiviral drugs have been developed, the emergence of viral variants and the limitations of current treatments reinforce the necessity of exploring alternative approaches. Medicinal plants, known for their bioactive compounds with antioxidant, anti-inflammatory, and antiviral properties, have gained attention as potential inhibitors of viral replication. This article presents a narrative review study that seeks to examine the antiviral potential of plant extracts against SARS-CoV-2, focusing on key species such as Perilla frutescens, Punica granatum L., Nerium oleander, Scutellaria baicalensis, and Vitis vinifera. These extracts have demonstrated promising inhibitory effects on critical viral mechanisms, including RNA replication, protease activity (e.g., 3CLPro), and viral entry into host cells. The study also discusses the immunomodulatory effects of these compounds, particularly in reducing cytokine storm-related inflammation, a hallmark of severe COVID-19 cases. Furthermore, some plant-based extracts, such as Perilla frutescens, show potential synergistic effects when combined with conventional antivirals like remdesivir. Despite promising in vitro and in vivo results, further preclinical and clinical studies are necessary to validate the efficacy and safety of these natural compounds. Given their accessibility, safety, and broad-spectrum antiviral properties, medicinal plant extracts represent a valuable avenue for the development of novel therapies against COVID-19 and other emerging viral infections. This review underscores the need for continued research into plant-derived bioactives as potential candidates for integrative antiviral strategies.